HIV treatment strategies across Central, Eastern and Southeastern Europe: New times, old problems - Papadopoulos, Antonios; Thomas, Konstantinos; Protopapas, Konstantinos; Antonyak, Sergii; Begovac, Josip; Dragovic, Gordana; Gökengin, Deniz; Aimla, Kersti; Krasniqi, Valbon; Lakatos, Botond; Mardarescu, Mariana; Matulionyte, Raimonda; et al. (HIV medicine, 2023)
INTRODUCTION: In the last decade, substantial differences in the epidemiology of, antiretroviral therapy (ART) for, cascade of care in and support to people with HIV in vulnerable populations have been observed between countries in Western Europe, Central Europe (CE) and Eastern Europe (EE). The aim of this study was to use a survey to explore whether ART availability and therapies have evolved in CE and EE according to European guidelines. METHODS: The Euroguidelines in Central and Eastern Europe (ECEE) Network Group conducted two identical multicentre cross-sectional online surveys in 2019 and 2021 concerning the availability and use of antiretroviral drugs (boosted protease inhibitors [bPIs], integrase inhibitors [INSTIs] and nucleoside reverse transcriptase inhibitors [NRTIs]), the introduction of a rapid ART start strategy and the use of two-drug regimens (2DRs) for starting or switching ART. We also investigated barriers to the implementation of these strategies in each region. RESULTS: In total, 18 centres participated in the study: four from CE, six from EE and eight from Southeastern Europe (SEE). Between those 2 years, older PIs were less frequently used and darunavir-based regimens were the main PIs (83%); bictegravir-based and tenofovir alafenamide-based regimens were introduced in CE and SEE but not in EE. The COVID-19 pandemic did not significantly interrupt delivery of ART in most centres. Two-thirds of centres adopted a rapid ART start strategy, mainly in pregnant women and to improve linkage of care in vulnerable populations. The main obstacle to rapid ART start was that national guidelines in several countries from all three regions did not support such as strategy or required laboratory tests first; an INSTI/NRTI combination was the most commonly prescribed regimen (75%) and was exclusively prescribed in SEE. 2DRs are increasingly used for starting or switching ART (58%), and an INSTI/NRTI was the preferred regimen (75%) in all regions and exclusively prescribed in SEE, whereas the use of bPIs declined. Metabolic disorders and adverse drug reactions were the main reasons for starting a 2DR; in the second survey, HIV RNA <500 000 c/ml and high cluster of differentiation (CD)-4 count emerged as additional important reasons. CONCLUSIONS: In just 2 years and in spite of the emergence of the COVID-19 pandemic, significant achievements concerning ART availability and strategies have occurred in CE, EE and SEE that facilitate the harmonization of those strategies with the European AIDS Clinical Society guidelines. Few exceptions exist, especially in EE. Continuous effort is needed to overcome various obstacles (administrative, financial, national guideline restrictions) in some countries.
Keywords: rapid ART strategy; Female; Europe; AIDS; maintenance therapy; ženské pohlaví; průřezové studie; Protease Inhibitors; HIV Infections; Anti-HIV Agents; initial therapy; lidé; Evropa; inhibitory proteas; těhotenství; antiretroviral therapy; COVID-19; HIV infekce; pandemie; Cross-Sectional Studies; southeastern Europe; antiretroviral drugs; Central Europe; Eastern Europe; HIV infection; látky proti HIV; Pregnancy; Pandemics; switch therapy; Humans